Intelligibility in world Englishes : theory and application - Nelson, Cecil L. (ESL and applied linguistics professional series., 2011)
Intelligibility is the term generally used to address the complex of criteria that describe how useful someone's English is when talking or writing to someone else. This textbook provides an overview of the definitions and scopes of intelligibility, comprehensibility and interpretability